Aggregation Gatekeeper and Controlled Assembly of Trpzip β-Hairpins - Markiewicz, Beatrice N. (American Chemical Society, 2014)
[Image: see text] Protein and peptide aggregation is an important issue both in vivo and in vitro. Herein, we examine the aggregation behaviors of two well-studied β-hairpins, Trpzip1 and Trpzip2. Previous studies suggested that Trpzip2 remains monomeric up to a concentration of ∼15 mM whereas Trpzip1 readily aggregates at micromolar concentrations at acidic or neutral pH. This disparity is puzzling considering that these two peptides differ only in their turn sequences (i.e., GN vs NG). We hypothesize that these peptides can aggregate from their folded states via native edge-to-edge interactions and that the Lys8 residue in Trpzip2 is a more effective aggregation gatekeeper, because of a more favorable orientation. In support of this hypothesis, we find that increasing the pH to 13 or replacing Lys8 with a hydrophobic and photolabile Lys analogue, Lys(nvoc), leads to a significant increase in the aggregation propensity of Trpzip2, and that the aggregation of this Trpzip2 mutant can be reversed upon restoring the native Lys side chain via photocleavage of the nvoc moiety. In addition, we find that while both Trpzip1 and Trpzip2 form parallel β-sheet aggregates, the Lys(nvoc) Trpzip2 mutant forms antiparallel β-sheets and more stable fibrils. Taken together, these findings provide another example showing how sensitive peptide and protein aggregation is to minor sequence variation and that it is possible to use a photolabile non-natural amino acid, such as Lys(nvoc), to tune the rate of peptide aggregation and to control fibrillar structure.